Hydrodynamic mechanism of quasi-synchronous water level rise in observation wells - Ding, Fenghe; Ma, Heqing; Luo, Guofu; Dai, Yong; He, Jiawei; Zhu, Pengtao; Wu, Xiaoyan (Frontiers in Earth Science, 2022)
In 2014, aquifers in the provinces of Jiangsu and Anhui exhibited abnormal and quasi-synchronous increases in water level of unknown origin. Based on the related theories of fluid and rock mechanics, and using atmospheric pressure and tidal effects, we analyzed the changes in the porosity and hydraulic conductivity of the aquifer media for three wells in Jiangsu (Su02, Su03, and Su18) and one well in Anhui (Dingyuan 04) in the undrained state. By constructing a dynamic change model of the well–aquifer system in two states (force and water balance), the hydrodynamic mechanism of the quasi-synchronous rise in the water level in each well was explored. The results show that the rise in the well water level was not related to aquifer compression but was mainly due to an increase in recharge and the recharge exceeding the discharge. These findings indicate that recharge caused by the infiltration of rainwater was the mechanism behind the observed anomaly.